2019
DOI: 10.1002/cre2.207
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy and bruxism: Effects of botulinum toxin injections—A randomized controlled trial

Abstract: ObjectiveCerebral palsy (CP) includes disturbances in muscular control caused by perinatal brain injury. Masticatory muscle involvement hampers functions such as chewing and talking. Bruxism and temporomandibular disorders are overrepresented. Neuromuscular blocks with botulinum toxin type A (BTX‐A) may alleviate problems due to muscular hyperactivity. The aim was to evaluate masticatory muscle BTX‐A injections in subjects with CP and bruxism.MethodsA prospective, parallel, randomized, placebo‐controlled, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…Previous studies have proved the efficacy of the two BoNT-A formulations in children with CP. 23,28,29 The tendency to choose Onabotulinumtoxin-A indicated that many caregivers The number of adverse events divided by the number of injections (1013 Onabotulinumtoxin-A injections, 418 Lanbotulinumtoxin-A injections).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have proved the efficacy of the two BoNT-A formulations in children with CP. 23,28,29 The tendency to choose Onabotulinumtoxin-A indicated that many caregivers The number of adverse events divided by the number of injections (1013 Onabotulinumtoxin-A injections, 418 Lanbotulinumtoxin-A injections).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we noticed that more families chose Onabotulinumtoxin‐A rather than Lanbotulinumtoxin‐A, even though the latter is much cheaper. Previous studies have proved the efficacy of the two BoNT‐A formulations in children with CP 23,28,29 . The tendency to choose Onabotulinumtoxin‐A indicated that many caregivers have less confidence in the safety of Lanbotulinumtoxin‐A than Onabotulinumtoxin‐A to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…A propósito de la dosis y lugar de punción del botox, no se ha evidenciado hasta la fecha una norma de la cantidad máxima para el tratamiento del bruxismo, debido a que la literatura reporta que el producto es comercializado en distintas disoluciones (Weill Medical College of Cornell University, 2021). Tampoco se ha establecido el número de punciones ni el mejor sitio en el que se obtengan mejores resultados; esto se puede corroborar en nuestra revisión, puesto que en ciertos artículos el sitio de las punciones van en un rango de 2 a 7 (Ondo et al, 2018) (Ali et al, 2021) (Yurttutan et al, 2019) pero en otras investigaciones no se detalla la cantidad exacta de punciones realizadas (Cahlin et al, 2019) (Shim et al, 2020). De la misma manera, no se ha establecido si existe mayor efectividad al colocar en el músculo masetero o temporal; en base a esto, 4 de los 6 artículos incluidos en la revisión aplicaron 100U de BTX en total; en otras palabras, en el músculo masetero y temporal de manera bilateral.…”
Section: Discussionunclassified
“…3,14,15 Several factors have been pointed out to justify the high prevalence of bruxism in this population, such as myofunctional disorder, hyperactivity of the muscles of the masticatory system, the inherent neurological changes and even disturbances in dopaminergic function. [15][16][17] One limitation found was the variability of diagnostic criteria and the lack of associated specificity, suggesting that studies need greater standardization of diagnostic protocols. Specifically in SB, the prevalence in this study was 14.5%, being lower than the results achieved in a similar Portuguese population, whose value was 28.8%.…”
Section: Discussionmentioning
confidence: 99%